From Antenatal Clue to Postnatal Cure: Surgical Management of a Symptomatic Jejunal Duplication Cyst in an Infant - Agung Hartanto; Agung Aji Prasetyo; Agoes Wibisono (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Alimentary tract duplication cysts represent a rare and challenging subset of congenital anomalies. Their non-specific symptomatology often leads to their misidentification as more common pediatric conditions, making a clear diagnostic pathway essential. With jejunal localization being particularly uncommon, these lesions can range from being asymptomatic to causing life-threatening abdominal emergencies. The evolution of high-resolution prenatal imaging, however, has fundamentally altered their management, enabling proactive postnatal intervention. Case presentation: A three-month-old female infant, with a history of a non-specific cystic intra-abdominal mass identified on a second-trimester antenatal ultrasound, was referred for progressive abdominal distension and non-bilious vomiting. Postnatal examination revealed a palpable right upper quadrant mass. A contrast-enhanced computed tomography (CT) scan confirmed a 3.9 x 3.9 x 3.3 cm thick-walled jejunal duplication cyst causing partial obstruction. The patient underwent a successful exploratory laparotomy with segmental jejunal resection and primary end-to-end anastomosis. The postoperative course was uneventful, with complete resolution of symptoms. Histopathology confirmed a benign jejunal duplication cyst without heterotopic mucosa. Conclusion: Jejunal duplication cysts are a critical, albeit rare, consideration in the differential diagnosis of an infant with an abdominal mass or intestinal obstruction. This case serves as a paradigm of modern perinatal care, where an antenatal clue facilitates a planned, definitive postnatal cure. Complete surgical resection remains the gold standard, preventing severe complications and ensuring an excellent long-term prognosis.